Preparation of a magnetic polystyrene nanocomposite for dispersive solid-phase extraction of copper ions in environmental samples - Ali Mehdinia (Nature Portfolio, 2020)
Abstract The core shell nanostructure of magnetic polystyrene (PS@Fe3O4) was prepared and its physic-chemical properties were studied FT-IR, SEM, TEM, VSM and BET + BJH. The new adsorbent was applied in the dispersive solid phase extraction technique for measuring copper ions in water, Soil and Oyster samples. Analysis is carried out using a flame atomic absorption spectrometry system. Effective parameters on extraction efficiency, such as pH of extraction solution, sorbent dosage, contact time, concentration and volume of desorption eluent and desorption time were optimized using one at a time method. N2 adsorption-desorption experiment resulted in high BET surface area (32.002 m2 g−1) and large pore volume (0.1794 cm3 g−1) for PS@ Fe3O4 nanocomposite. Under the optimum conditions, a calibration curve within the range of 5–40 ng mL−1 with an appropriate coefficient of determination (R2) of 0.9946 was obtained. Preconcentration factor (PF) and limit of detection (LOD) were found to be 55 and 1.6 ng mL−1, respectively. The repeatability and reproducibility for three replicate measurements at the concentration of 25 ng mL−1 were 2.5%–1.4%, respectively. The Freundlich adsorption isotherm and pseudo-second-order kinetic model were consistent to experimental data in adsorption mechanism study. The maximum adsorption capacity was 19.56 mg g−1 for Cu (II). Finally, the efficiency of the method was investigated for analysis of the copper in environmental samples and good relative recoveries (RR%) were obtained within the range of 99.2% to 101.2%.